Potential for endozoochorous seed dispersal by sheep and goats: Risk of weed seed transport via animal faeces. (8th December 2020) - Oveisi, Mostafa; Ojaghi, Ahmad; Rahimian Mashhadi, Hamid; Müller‐Schärer, Heinz; Reza Yazdi, Kamran; Pourmorad Kaleibar, Behnaz; Soltani, Elias
Abstract: Endozoochory is known as an important mechanism for the spread of weeds. We carried out experiments to assess the fate of seeds of several weed species ( Convolvulus arvensis, Cuscuta campestris, Rumex crispus, Hordeum spontaneum and Sorghum halepense ) after passing through the gut of sheep and goat. Eighteen animals of both sheep and goat received diet mixed with seeds of the weed species or control with only wheat bran (five weed species + control × three replications). Results showed that a higher proportion of seeds were missing after passage through the sheep gut than in goats. In goats, a greater proportion of seeds were dead after passage, but the number of seeds collected from dung was also greater. Weed species differed, with the highest seed recovery and viability in Cuscuta campestris . Based on time of seed passages through the animal gut estimated for the different weed species, we recommend that sheep should be kept in a corral for 96 hr to minimise seed transportation via their faeces. For goats, if R. crispus and C. arvensis seeds could be excluded from the diet, then maintaining them for 96 hr in an animal stall would ensure little seed transportation via dung, but we found R. crispus and C. arvensis seeds to be present and viable in goat dung even 120 hr after feeding. Very large numbers of viable seeds can be found in goat and sheep dung, so the use of rotted manure is highly recommended to avoid transportation of viable seeds via manure fertilisers.